Preparation method and application of iron-based lattice molecular catalyst
By collecting unit A lattice molecules into organic polymers, the iron-based polygrid molecules (FePAG) catalysts were solved, and the existing CO2 electrocatalytic reduction catalysts were effectively reduced to methanol with high efficiency and stability.
Patent Information
- Application Number
- CN202411062967.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-08-05
AI Technical Summary
The existing CO2 electrocatalytic reduction catalysts have poor activity, poor selectivity and poor stability in reducing CO2 to methanol, making it difficult to achieve efficient deep reduction.
By collecting unit A lattice molecules into organic polymers, an iron-based polygrid molecule (FePAG) catalyst is prepared, which has non-planar, large steric hindrance, high conjugation and rigid geometric characteristics, and can efficiently and stably reduce CO2 to methanol.
It has achieved efficient and stable reduction of CO2 to methanol, solved the shortcomings of existing catalysts in terms of activity, selectivity and stability, and has better market application prospects.
Smart Images

Figure CN118978671B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysis, and in particular relates to a preparation method and application of an iron-based polylattice molecule (FePAG) catalyst. Background Art
[0002] Human activities continue to increase carbon dioxide (CO 2 ) emissions, causing atmospheric CO 2 The increase in concentration has triggered the greenhouse effect, leading to global climate change and environmental problems. In order to meet this challenge, the use of renewable energy for CO 2 Electrocatalytic reduction to produce fuels and high-value-added chemicals has been recognized as a sustainable and zero-emission carbon cycle solution. 2 The inherent chemical inertness of CO and the competitive hydrogen evolution reaction (HER) limit the 2 The realization of efficient conversion and high product selectivity. Therefore, researchers have been committed to developing electrocatalysts with high activity, high selectivity and high stability.
[0003] Currently, CO 2 Electrocatalytic reduction catalysts mainly include metal alloy catalysts, metal oxide catalysts, single atom catalysts, metal-organic complex catalysts, molecular catalysts, etc. Among them, molecular catalysts, such as metalloporphyrins and metal phthalocyanines, have attracted much attention because they can adjust the primary and secondary coordination spheres by manipulating the coordination environment and the stereo and electronic effects of the ligands to adjust the catalytic efficiency and product selectivity. Integrating molecular catalysts into covalent organic polymers is an important approach to designing efficient CO 2 Another strategy for electrocatalysts of reduction reactions is that in this approach, molecular catalysts are present as uniformly dispersed active sites in a covalent organic polymer framework. At the same time, by controlling the adjacent functional groups in the framework, the electronic structure of the active sites can be adjusted, providing an opportunity to regulate the intrinsic catalytic properties of the catalyst. Currently, although cobalt-based molecular catalysts and their combination with covalent organic polymers have been widely studied, the main product is still carbon monoxide, and there are few reports on the generation of deep reduction products such as methanol. Therefore, the development of CO 2 Efficient deep reduction catalysts remain one of the important research topics.
[0004] The present invention integrates unit A-type lattice molecules into organic polymers to prepare iron-based polylattice molecules (FePAG) catalysts, which can efficiently and stably convert CO 2 Reduced to methanol. Summary of the invention
[0005] Purpose of the invention: To convert CO 2The present invention provides a method for preparing an iron-based polylattice molecule (FePAG) catalyst and its application. Based on the unique chemical structure of the molecular catalyst, the iron-based polylattice molecule (FePAG) catalyst prepared by the present invention can convert CO into methanol with high activity, high selectivity and high stability. 2 Reduction to methanol to promote CO 2 It provides theoretical and technical guidance for emission reduction and resource utilization.
[0006] Technical content: An iron-based polymerized molecular catalyst, the general structure of which is as follows:
[0007]
[0008] A method for preparing an iron-based polymerized molecular catalyst comprises the following steps:
[0009] Step 1: Add 3,6-dibromocarbazole, ethyl bromide, sodium hydroxide and tetrabutylammonium bromide into a three-necked flask, then add acetone, and stir in an oil bath at 60-70° C. for 1.5-3 hours to obtain 3,6-dibromoethylcarbazole;
[0010] Step 2: Put 3,6-dibromoethylcarbazole, biphenylphosphinoyl ferrocene and potassium acetate into a sealed flask, evacuate and blow nitrogen, and inject [1,1'-bis(diphenylphosphino)ferrocene]palladium dichloride and dry 1,4-dioxane into the flask under nitrogen protection, respectively, and react at 100-110° C. for 8-15 hours to obtain 9-ethyl-3,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-9H-carbazole;
[0011] Step 3, preparing 2,7-dibromo-9-(4-(octyloxy)phenyl)-9H-fluoren-9-ol;
[0012] Step 3.1, add Mg chips into a flask, and then add iodine particles; seal the flask, evacuate and purify with nitrogen, and slowly inject 1-bromo-4-(octyloxy)benzene and tetrahydrofuran into the flask in batches under nitrogen protection, and after the injection, reflux at 70-90° C. for 3-6 hours to obtain the Grignard reagent;
[0013] Step 3.2, then under nitrogen protection, add the prepared Grignard reagent dropwise into a reaction bottle containing 2,7-dibromofluorenone and tetrahydrofuran, and ensure that the temperature in the reaction bottle is in the range of 0 to 10° C.; after the dropwise addition is completed, reflux at 80 to 90° C. for 5 to 8 hours to obtain 2,7-dibromo-9-(4-(octyloxy)phenyl)-9H-fluoren-9-ol;
[0014] Step 4: 9-ethyl-3,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-9H-carbazole, 2,7-dibromo-9-(4-(octyloxy)phenyl)-9H-fluorene-9-ol and Pd(PPh 3 ) 4 The catalyst was added to a three-necked flask; then, the reaction system was evacuated and replaced with nitrogen several times to ensure an oxygen-free environment; a mixture of toluene and tetrahydrofuran bubbled with nitrogen and K 2 CO 3 / KF aqueous solution is added to the flask; the reaction system is sealed and connected to a nitrogen balloon, and the reaction is stirred in an oil bath at 90-100°C for 1.5-3 hours to obtain the synthon BOH;
[0015] Step 5: Place 4-methyl-N,N-diphenylaniline in a reaction flask, add dichloromethane to dissolve to obtain a 4-methyl-N,N-diphenylaniline solution, and then add BF 3 ·Et 2 O; dissolving BOH in dichloromethane to obtain a BOH solution, placing the BOH solution in a constant pressure dropping funnel; slowly dropping the BOH solution into the reaction bottle at room temperature, and continuing to stir for 5 to 10 minutes after the dropping is completed, to obtain compound BG;
[0016] Step 6: In a light-proof nitrogen environment in a glove box, add BG and toluene to a flask to obtain a BG solution; add bipyridine and bis(1,5-cyclooctadiene) nickel to a dry reaction tube in a light-proof nitrogen environment in a glove box, seal the tube, and gradually add 1,5-cyclooctadiene and N,N-dimethylformamide to the reaction tube with a syringe; preheat the reaction tube in a 65-75°C oil bath for 20-40 minutes, and then add the BG solution to the reaction tube in a nitrogen environment; then heat the oil bath to 80-90°C and stir to react for 4-6 days, then add a capping agent, bromobenzene, to cap the tube, and continue to react for 1-2 days to obtain a polylattice molecule PAG;
[0017] Step 7: Add the polylattice molecule PAG to the flask, followed by dichloromethane; then add FeCl 3 The ethanol solution is added into the flask; the reaction mixture is stirred at room temperature for 10 to 15 hours to obtain the iron-based polymer molecule FePAG.
[0018] Further, in step 1, the molar ratio of ethyl bromide to 3,6-dibromocarbazole is 1:1 to 1.5:1; the molar ratio of sodium hydroxide to 3,6-dibromocarbazole is 1:2 to 1.5:1; the molar ratio of tetrabutylammonium bromide to 3,6-dibromocarbazole is 1:20 to 1:5; acetone is used as a solvent, and the concentration of 3,6-dibromocarbazole is 0.1 to 0.3M;
[0019] In step 2, the molar ratio of pinacol diboron to 3,6-dibromoethylcarbazole is 2:1-5:1; the molar ratio of potassium acetate to 3,6-dibromoethylcarbazole is 3:1-5:1; the molar ratio of [1,1'-bis(diphenylphosphino)ferrocene]palladium dichloride to 3,6-dibromoethylcarbazole is 1:20-3:20; 1,4-dioxane is used as a solvent, and the concentration of 3,6-dibromoethylcarbazole is 0.15-0.3M;
[0020] In step 3.1, the molar ratio of Mg chips to 1-bromo-4-(octyloxy)benzene is 1:2 to 1:1; 2 The molar ratio of tetrahydrofuran to 1-bromo-4-(octyloxy)benzene is 1:210 to 1:52.5; tetrahydrofuran is used as a solvent, and the concentration of 1-bromo-4-(octyloxy)benzene is 1 to 3M;
[0021] In step 3.2, the molar ratio of 2,7-dibromofluorenone to 1-bromo-4-(octyloxy)benzene in step 3.1 is 1:4 to 1:2; tetrahydrofuran is used as a solvent, and the concentration of 2,7-dibromofluorenone is 0.25 to 0.6 M;
[0022] In step 4, the molar ratio of 2,7-dibromo-9-(4-(octyloxy)phenyl)-9H-fluorene-9-ol and 9-ethyl-3,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-9H-carbazole is 2:1 to 4:1; Pd(PPh 3 ) 4 The molar ratio of K to 9-ethyl-3,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-9H-carbazole is 1:7 to 1:3; 2 CO 3 The molar ratio of KF to 9-ethyl-3,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-9H-carbazole is 1:1 to 4:1; the molar ratio of KF to 9-ethyl-3,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-9H-carbazole is 1:1 to 4:1; the concentration of 9-ethyl-3,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-9H-carbazole is 0.15 to 0.3 M; 2 CO 3 / The concentration of KF aqueous solution is 1.5~3M;
[0023] In step 5, BF 3 ·Et 2The molar ratio of O to BOH is 7:1 to 15:1; the molar ratio of 4-methyl-N,N-diphenylaniline to BOH is 1:1 to 1.5:1; the concentration of 4-methyl-N,N-diphenylaniline solution is 1 to 4 mM; the concentration of BOH solution is 1 to 4 mM;
[0024] In step six, the molar ratio of bipyridine to BG is 3:1 to 5:1; the molar ratio of bis(1,5-cyclooctadiene)nickel to BG is 3:1 to 5:1; the molar ratio of 1,5-cyclooctadiene to BG is 3:1 to 5:1; the volume ratio of N,N-dimethylformamide to toluene is 1:14 to 1:3; the volume ratio of bromobenzene to toluene is 1:15 to 1:5; the concentration of BG in toluene is 0.05 to 0.2 M;
[0025] In step 7, FeCl 3 The mass ratio of dichloromethane to ethanol is 1:1 to 2:1.
[0026] The iron-based polymerized lattice molecules prepared by the present invention are used to prepare a working electrode, and the working electrode is used to convert CO 2 Reduced to methanol. The preparation steps of the working electrode are as follows:
[0027] Step (1), adding the iron-based polymer molecule FePAG to ethanol, then adding the Nafion solution, and ultrasonicating for 30 minutes to fully disperse it;
[0028] Step (2), taking 100 μL of the solution prepared in step (1) and evenly applying it on carbon paper, and then drying it naturally to obtain a working electrode of an H-type electrolytic cell;
[0029] Step (3), take 100 μL of the solution prepared in step (1) and evenly apply it on the Sigracet 29BC gas diffusion layer, and then dry it naturally to obtain the working electrode of the flow-type electrolytic cell.
[0030] Furthermore, in step (1), after the iron-based polymer molecule FePAG is added to ethanol, the amount of FePAG in the ethanol is 0.005-0.02 mg / μL; the concentration of the added Nafion solution is 5 wt.%, and the volume ratio of the Nafion solution to the ethanol is 1:20-1:5;
[0031] In step (2), 100 μL of the solution prepared in step (1) is evenly dropped on carbon paper;
[0032] In step (3), 100 μL of the solution prepared in step (1) is evenly drop-coated on the Sigracet 29BC gas diffusion layer. Compared with the prior art, the present invention has the following advantages:
[0033] 1) The iron-based polylattice molecule (FePAG) prepared by the present invention has non-planar, large steric hindrance, high conjugation and rigid geometric structure characteristics. The non-planar and large steric hindrance molecular structure can effectively inhibit the aggregation of molecules and is conducive to the high exposure of active sites; the highly conjugated molecular structure promotes the efficient transfer of electrons; and the rigid geometric structure is conducive to stabilizing the active sites.
[0034] 2) The iron-based polylattice molecules (FePAG) prepared by the present invention can efficiently and stably catalyze CO 2 Electrochemical reduction to produce methanol solves the problem of molecular electrocatalysts in CO 2 It has better market application prospects by overcoming the problems of poor activity, poor selectivity and poor stability in reduction to methanol.
[0035] 3) The iron-based polymerized molecular catalyst prepared by the present invention can not only effectively catalyze CO 2 The conversion and utilization of CO2 can alleviate the greenhouse effect and provide a more environmentally friendly and sustainable way for traditional methanol production. 2 Resource utilization provides an efficient method. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 FePAG catalyst prepared in Example 1 is used for CO at different potentials in H-type electrolyzer 2 Distribution diagram of Faraday efficiency of reduction products;
[0037] Figure 2 The FePAG catalyst prepared in Example 1 was used for CO 2 Selectivity test results of reduction to methanol;
[0038] Figure 3 The FePAG catalyst prepared in Example 1 was used for CO 2 Reduction stability test results;
[0039] Figure 4 FePAG catalyst prepared in Example 1 reduces CO at different potentials in an H-type electrolyzer 2 The production rate of methanol is obtained;
[0040] Figure 5 FePAG catalyst prepared in Example 1 is used for CO at different potentials in a flow-type electrolyzer. 2 Faradaic efficiency and current density distribution of the reduction product methanol;
[0041] Figure 6 The synthetic route of the iron-based polylattice molecule (FePAG) in Example 1;
[0042] Figure 6In the figure, the compounds represented by 1-9 are: 1 is 3,6-dibromocarbazole; 2 is ethyl bromide; 3 is 3,6-dibromoethylcarbazole; 4 is biphenylboronate; 5 is 9-ethyl-3,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-9H-carbazole; 6 is 1-bromo-4-(octyloxy)benzene; 7 is 2,7-dibromofluorenone; 8 is 2,7-dibromo-9-(4-(octyloxy)phenyl)-9H-fluoren-9-ol; 9 is 4-methyl-N,N-diphenylaniline; and 10 is ferric chloride. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is described in detail below with reference to the accompanying drawings, but the protection scope of the present invention is not limited to the embodiments.
[0044] Example 1: Preparation of FePAG
[0045] like Figure 6 As shown, the preparation steps of the iron-based polylattice molecule (FePAG) disclosed in the present invention are as follows:
[0046] Step 1, 3,6-dibromocarbazole (15g, 46.2mmol), bromoethane (5g, 46.2mmol), sodium hydroxide (1.8g, 46.2mmol), tetrabutylammonium bromide (1.5g, 4.62mmol) and acetone (308mL) were added to a three-necked flask in sequence, and refluxed and stirred in an oil bath at 65°C for 2 hours. After the reaction, the organic phase was extracted with dichloromethane. Then it was dried with anhydrous sodium sulfate, filtered, and the solvent was evaporated under reduced pressure. The crude product was separated and purified by column chromatography with 200-300 mesh silica gel to obtain compound 3,6-dibromoethylcarbazole;
[0047] Step 2: Put 3,6-dibromoethylcarbazole (3 g, 8.5 mmol), biboric acid pinacol ester (6.5 g, 25.5 mmol) and potassium acetate (3.3 g, 34 mmol) into a flask, seal it, wrap it with tin foil, and evacuate and blow nitrogen for 3 times;
[0048] Then add Pd(dppf)Cl 2 ([1,1'-bis(diphenylphosphino)ferrocene]palladium dichloride) (435 mg, 0.6 mmol);
[0049] Subsequently, the device was evacuated and nitrogen-filled again; dry 1,4-dioxane (43 mL) was injected into the flask under nitrogen protection and reacted at 105°C for 12 hours. After the reaction, the organic phase was extracted with dichloromethane. Then it was dried with anhydrous sodium sulfate, filtered, and the solvent was evaporated under reduced pressure. The crude product was separated and purified by column chromatography using 200-300 mesh silica gel to obtain 9-ethyl-3,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-9H-carbazole;
[0050] Step 3: Mg chips (3.4 g, 140 mmol) were added to the flask, followed by I 2 (254mg, 1mmol). The device was sealed and vacuumed and nitrogen was added. Under nitrogen protection, 1-bromo-4-(octyloxy)benzene (30g, 105mmol) and tetrahydrofuran (52mL) were slowly injected into the flask in 5 batches, with 6g of 1-bromo-4-(octyloxy)benzene and about 10.4mL of tetrahydrofuran injected in each batch. After the injection was completed, the reaction was refluxed at 85℃ for 4h to obtain the Grignard reagent.
[0051] Then, under nitrogen protection, the prepared Grignard reagent is added dropwise to a reaction bottle containing 2,7-dibromofluorenone (11.9 g, 35 mmol) and tetrahydrofuran (75 mL), and the temperature in the reaction bottle is ensured to be in the range of 0 to 10 ° C. The entire dropwise addition process takes 20 to 50 minutes; after the dropwise addition is completed, the reaction is refluxed at 85 ° C for 6 hours. After the reaction is completed, the reaction is quenched with a saturated ammonium chloride solution, the tetrahydrofuran solvent is removed by rotary evaporation, and then a large amount of water is added to precipitate the solid, and the inorganic salt is removed by stirring. Filter and wash with a large amount of deionized water to obtain a crude product. The crude product is separated and purified by column chromatography using 200-300 mesh silica gel to obtain 2,7-dibromo-9-(4-(octyloxy)phenyl)-9H-fluoren-9-ol.
[0052] Step 4: 9-ethyl-3,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-9H-carbazole (3 g, 6.7 mmol), 2,7-dibromo-9-(4-(octyloxy)phenyl)-9H-fluoren-9-ol (11 g, 20.2 mmol) and Pd(PPh 3 ) 4 The catalyst (1.5 g, 1.3 mmol) (protected from light) was added into a three-necked flask.
[0053] Subsequently, the reaction system was vacuumed and replaced with nitrogen several times to ensure an oxygen-free environment. A nitrogen-bubbled toluene / tetrahydrofuran mixture (volume ratio 1:1, 20.2 mL) and K 2 CO 3 / KF aqueous solution (molar ratio 1:1, 2M, 13.4 mL) was injected into the flask.
[0054] The reaction system was sealed and connected to a nitrogen balloon, and the reaction was stirred in a 95°C oil bath for 2 hours. After the reaction was completed, the organic phase was extracted with dichloromethane. Then it was dried with anhydrous sodium sulfate, filtered, and the solvent was evaporated under reduced pressure. The crude product was separated and purified by column chromatography using 200-300 mesh silica gel to obtain the synthon BOH.
[0055] Step 5: Place 4-methyl-N,N-diphenylaniline (69.4 mg, 0.268 mmol) in a reaction flask and add dichloromethane (134 mL) to dissolve. Then add BF 3 ·Et 2 O (401.7 mg, 2.83 mmol), BOH (300 mg, 0.268 mmol) was dissolved in dichloromethane (134 mL) and placed in a constant pressure dropping funnel. The BOH solution was slowly added dropwise to the reaction bottle for about 2 hours, and stirring was continued for 5 minutes after the addition was completed. After the reaction was completed, the organic phase was extracted with dichloromethane. Then it was dried over anhydrous sodium sulfate, filtered, and the solvent was evaporated under reduced pressure. The crude product was separated and purified by column chromatography using 200-300 mesh silica gel to obtain BG.
[0056] Step 6: Preparation of polylattice molecules (PAG):
[0057] 1) In a light-proof nitrogen environment in a glove box, add BG (148 mg, 0.11 mmol) and toluene (10 mL) into a flask to obtain a BG solution;
[0058] 2) Add bipyridine (69.3 mg, 0.44 mmol) and bis(1,5-cyclooctadiene)nickel (120.7 mg, 0.44 mmol) into a dry reaction tube in a light-proof nitrogen environment in a glove box. After sealing, gradually add 1,5-cyclooctadiene (0.6 mL, 0.44 mmol) and N,N-dimethylformamide (2 mL) into the reaction tube using a syringe;
[0059] 3) Preheat the reaction tube in a 70°C oil bath for half an hour, and then transfer the BG solution in the flask to the reaction tube under nitrogen atmosphere;
[0060] 4) The oil bath was then heated to 85°C and stirred for 5 days, after which bromobenzene (1 mL) was added for end-capping and the reaction was continued for 1 day. After the reaction was completed, a 10 cm cotton column filled with neutral alumina was used to press the column with THF to remove the Ni catalyst. The DMF was then repeatedly washed with methanol to remove the DMF, and the solid was subjected to Soxhlet extraction to obtain the polylattice molecule (PAG).
[0061] Step 7: PAG (100 mg) was added to the flask, followed by dichloromethane (50 mL). 3 (27.3 mg) in ethanol (25 mL) was added to the flask. The reaction mixture was stirred at room temperature for 12 hours. After the reaction was completed, the solvent was evaporated under reduced pressure; then, it was washed with deionized water and centrifuged to remove the unreacted FeCl 3 , and the iron-based polymer molecule FePAG is obtained.
[0062] Example 2: Preparation of working electrode based on the iron-based polylattice molecule (FePAG) in Example 1
[0063] The preparation steps of the working electrode are as follows:
[0064] (1) Preparation of H-type electrolytic cell working electrode:
[0065] Step (1), adding the FePAG complex (2 mg) to ethanol (200 μL), followed by adding 5 wt.% Nafion solution (20 μL), and ultrasonicating for 30 minutes to fully disperse it;
[0066] Step (2): Take 100 μL of the solution prepared in step (1) and evenly apply it on a piece of carbon paper (1×1 square centimeter), and then dry it naturally.
[0067] (2) Preparation of working electrodes for flow-type electrolytic cells:
[0068] Step (1), adding the FePAG complex (2 mg) to ethanol (200 μL), followed by adding 5 wt.% Nafion solution (20 μL), and ultrasonicating for 30 minutes to fully disperse it;
[0069] Step (2) Take 100 μL of the solution prepared in step (1) and evenly apply it on the Sigracet 29BC gas diffusion layer (GDL, Sigracet 29BC), and then dry it naturally.
[0070] Test Example 1: Using the H-type electrolyzer working electrode and the flow-type electrolyzer working electrode prepared in Example 2, CO 2 Reduced to methanol, the specific test method is as follows:
[0071] (1) In the test of H-type electrolytic cell, Ag / AgCl and platinum sheet were used as reference electrode and counter electrode respectively, and FePAG was used as working electrode. The cathode chamber and anode chamber were separated by Nafion 117 proton exchange membrane. Each chamber was filled with 20 ml of 0.5 M KHCO 3 Before all electrochemical measurements, CO was introduced into the cathode chamber for half an hour.2 Make CO 2 The dissolution in the electrolyte reaches saturation. During the electrolysis process, control the CO 2 The flow rate is 20 sccm.
[0072] (2) In the flow-type electrolyzer test, FePAG was used as the working electrode, Ag / AgCl and iridium oxide-loaded titanium mesh (IrO 2 / Ti mesh) were used as reference electrode and counter electrode respectively. The cathode chamber and anode chamber were separated by Nafion 117 membrane. During the electrolysis process, CO 2 The flow rate was 30 sccm. 0.1 M KOH + 3 M KCl and 1 M KOH electrolytes were continuously circulated in the cathode chamber and the anode chamber at a flow rate of 20 mL / min, respectively. The electrochemical measurements were controlled and recorded using a CHI 650E potentiometer. The gaseous products were monitored by online gas chromatography (GC 7890B, Agilent), while the liquid products after the reaction were monitored by nuclear magnetic resonance (600 MHz 1 H NMR, Bruker Advance).
[0073] (3) Test results are as follows Figures 1 to 5 As shown:
[0074] Figure 1 The FePAG catalyst is used for the CO 2 Distribution diagram of the Faraday efficiency of reduction products. Methanol is the only liquid product, and its Faraday efficiency is the highest at -0.8V, reaching 60.5%.
[0075] Figure 2 FePAG catalyst for CO in H-type electrolyzer 2 The selectivity test result of reduction to produce methanol showed that the selectivity of methanol was 98.3% at -0.8V.
[0076] Figure 3 FePAG catalyst in H-type electrolyzer at -0.8V CO 2 The reduction stability test results show that the catalyst can work stably for 100 hours.
[0077] Figure 4 FePAG catalyst for CO reduction at different potentials in H-type electrolyzer 2 The methanol production rate was 9.8 μmol h at -0.8 V. -1 cm -2 .
[0078] Figure 5 The FePAG catalyst is used for the CO2 The Faraday efficiency and current density distribution of the reduction product methanol. At -0.7V, the methanol Faraday efficiency is the highest, reaching 64.2%, and the current density of methanol is 131mAcm -2 .
[0079] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention as defined in the appended claims.
Claims
1. An iron-based polylattice molecular catalyst, characterized in that: The general structure is as follows:
2. The method for preparing the iron-based polymerized molecular catalyst according to claim 1, characterized in that: The steps include: Step 1: Add 3,6-dibromocarbazole, ethyl bromide, sodium hydroxide and tetrabutylammonium bromide into a three-necked flask, then add acetone, and stir in an oil bath at 60-70° C. for 1.5-3 hours to obtain 3,6-dibromoethylcarbazole; Step 2: Put 3,6-dibromoethylcarbazole, biphenylphosphinoyl ferrocene and potassium acetate into a sealed flask, evacuate and blow nitrogen, and inject [1,1'-bis(diphenylphosphino)ferrocene]palladium dichloride and dry 1,4-dioxane into the flask under nitrogen protection, respectively, and react at 100-110° C. for 8-15 hours to obtain 9-ethyl-3,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-9H-carbazole; Step 3, preparing 2,7-dibromo-9-(4-(octyloxy)phenyl)-9H-fluoren-9-ol; Step 3.1, add Mg chips into a flask, and then add iodine particles; seal the flask, evacuate and purify with nitrogen, and slowly inject 1-bromo-4-(octyloxy)benzene and tetrahydrofuran into the flask in batches under nitrogen protection, and after the injection, reflux at 70-90° C. for 3-6 hours to obtain the Grignard reagent; Step 3.2, then under nitrogen protection, add the prepared Grignard reagent dropwise into a reaction bottle containing 2,7-dibromofluorenone and tetrahydrofuran, and ensure that the temperature in the reaction bottle is in the range of 0 to 10° C.; after the dropwise addition is completed, reflux at 80 to 90° C. for 5 to 8 hours to obtain 2,7-dibromo-9-(4-(octyloxy)phenyl)-9H-fluoren-9-ol; Step 4: Add 9-ethyl-3,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-9H-carbazole, 2,7-dibromo-9-(4-(octyloxy)phenyl)-9H-fluorene-9-ol and Pd(PPh3)4 catalyst into a three-necked flask; then, evacuate and replace the reaction system with nitrogen several times to ensure an oxygen-free environment; add a mixture of toluene and tetrahydrofuran bubbled with nitrogen and a K2CO3 / KF aqueous solution into the flask through a syringe; seal the reaction system and connect a nitrogen balloon, and stir the reaction in an oil bath at 90-100°C for 1.5-3 hours to obtain the synthon BOH; Step 5, 4-methyl-N,N-diphenylaniline is placed in a reaction bottle, dichloromethane is added to dissolve to obtain a 4-methyl-N,N-diphenylaniline solution, and then BF3·Et2O is added thereto; BOH is dissolved in dichloromethane to obtain a BOH solution, and the BOH solution is placed in a constant pressure dropping funnel; the BOH solution is slowly added dropwise to the reaction bottle at room temperature, and stirring is continued for 5 to 10 minutes after the addition is completed to obtain compound BG; Step 6: In a light-proof nitrogen environment in a glove box, add BG and toluene to a flask to obtain a BG solution; add bipyridine and bis(1,5-cyclooctadiene) nickel to a dry reaction tube in a light-proof nitrogen environment in a glove box, seal the tube, and gradually add 1,5-cyclooctadiene and N,N-dimethylformamide to the reaction tube with a syringe; preheat the reaction tube in a 65-75°C oil bath for 20-40 minutes, and then add the BG solution to the reaction tube in a nitrogen environment; then heat the oil bath to 80-90°C and stir to react for 4-6 days, then add a capping agent, bromobenzene, to cap the tube, and continue to react for 1-2 days to obtain a polylattice molecule PAG; Step 7: Add the polylattice molecule PAG into a flask, followed by dichloromethane; then add the ethanol solution of FeCl3 into the flask; stir the reaction mixture at room temperature for 10 to 15 hours to obtain the iron-based polylattice molecule FePAG.
3. The method for preparing the iron-based polymerized molecular catalyst according to claim 2, characterized in that: In step 1, the molar ratio of ethyl bromide to 3,6-dibromocarbazole is 1:1 to 1.5:1; the molar ratio of sodium hydroxide to 3,6-dibromocarbazole is 1:2 to 1.5:1; the molar ratio of tetrabutylammonium bromide to 3,6-dibromocarbazole is 1:20 to 1:5; acetone is used as a solvent, and the concentration of 3,6-dibromocarbazole is 0.1 to 0.3M; In step 2, the molar ratio of pinacol diboron to 3,6-dibromoethylcarbazole is 2:1-5:1; the molar ratio of potassium acetate to 3,6-dibromoethylcarbazole is 3:1-5:1; the molar ratio of [1,1'-bis(diphenylphosphino)ferrocene]palladium dichloride to 3,6-dibromoethylcarbazole is 1:20-3:20; 1,4-dioxane is used as a solvent, and the concentration of 3,6-dibromoethylcarbazole is 0.15-0.3M; In step 3.1, the molar ratio of Mg turnings to 1-bromo-4-(octyloxy)benzene is 1:2 to 1:1; the molar ratio of I2 to 1-bromo-4-(octyloxy)benzene is 1:210 to 1:52.5; tetrahydrofuran is used as a solvent, and the concentration of 1-bromo-4-(octyloxy)benzene is 1 to 3M; In step 3.2, the molar ratio of 2,7-dibromofluorenone to 1-bromo-4-(octyloxy)benzene in step 3.1 is 1:4 to 1:2; tetrahydrofuran is used as a solvent, and the concentration of 2,7-dibromofluorenone is 0.25 to 0.6 M; In step 4, the molar ratio of 2,7-dibromo-9-(4-(octyloxy)phenyl)-9H-fluorene-9-ol and 9-ethyl-3,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-9H-carbazole is 2:1 to 4:1; the molar ratio of Pd(PPh3)4 and 9-ethyl-3,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-9H-carbazole is 1:7 to 1:3; the molar ratio of K2CO3 and 9-ethyl-3,6-bis(4,4,5 The molar ratio of KF to 9-ethyl-3,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-9H-carbazole is 1:1 to 4:1; the molar ratio of KF to 9-ethyl-3,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-9H-carbazole is 1:1 to 4:1; the concentration of 9-ethyl-3,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-9H-carbazole is 0.15 to 0.3 M; the concentration of K2CO3 / KF aqueous solution is 1.5 to 3 M; In step 5, the molar ratio of BF3·Et2O to BOH is 7:1 to 15:1; the molar ratio of 4-methyl-N,N-diphenylaniline to BOH is 1:1 to 1.5:1; the concentration of the 4-methyl-N,N-diphenylaniline solution is 1 to 4 mM; the concentration of the BOH solution is 1 to 4 mM; In step six, the molar ratio of bipyridine to BG is 3:1 to 5:1; the molar ratio of bis(1,5-cyclooctadiene)nickel to BG is 3:1 to 5:1; the molar ratio of 1,5-cyclooctadiene to BG is 3:1 to 5:1; the volume ratio of N,N-dimethylformamide to toluene is 1:14 to 1:3; the volume ratio of bromobenzene to toluene is 1:15 to 1:5; the concentration of BG in toluene is 0.05 to 0.2 M; In step seven, the mass ratio of FeCl3 to PAG is 1:5 to 1:2; the volume ratio of dichloromethane to ethanol is 1:1 to 2:
1.
4. The use of the iron-based polylattice molecular catalyst according to claim 1, characterized in that: The iron-based polymer molecule is used to prepare a working electrode, and the working electrode is used to reduce CO2 into methanol.
5. The use of the iron-based polymerized molecular catalyst according to claim 4, characterized in that: The preparation steps of the working electrode are as follows: Step (1), adding the iron-based polymer molecule FePAG to ethanol, then adding the Nafion solution, and ultrasonicating for 30 minutes to fully disperse it; Step (2), taking 100 μL of the solution prepared in step (1) and evenly applying it on carbon paper, and then naturally drying it to obtain a working electrode of an H-type electrolytic cell; or, taking 100 μL of the solution prepared in step (1) and evenly applying it on a Sigracet 29BC gas diffusion layer, and then naturally drying it to obtain a working electrode of a flow-type electrolytic cell.
6. The use of the iron-based polymerized molecular catalyst according to claim 5, characterized in that: In step (1), after the iron-based polymer molecule FePAG is added to ethanol, the amount of FePAG in the ethanol is 0.005-0.02 mg / μL; the concentration of the added Nafion solution is 5 wt.%, and the volume ratio of the Nafion solution to the ethanol is 1:20-1:5.
Citation Information
Patent Citations
Organic conjugated nano poly-lattice, and preparation method and applications thereof
CN110092890A
Preparation method of iron-based supramolecular catalyst
CN116640161A